Subcytotoxic transepidermal delivery using low intensity cold atmospheric plasma - Ga Ram Ahn; Hyung-Joon Park; Yu Jin Kim; Min Gyo Song; Hye Sung Han; Woo Geon Lee; Hyuck Ki Hong; Kwang Ho Yoo; Joon Seok; Kyu Back Lee; Beom Joon Kim (Scientific Reports)
Abstract Cold atmospheric plasma (CAP) has been utilized in various medical devices using its oxidative nature. Recent studies have provided evidence that CAP can facilitate the delivery of large, hydrophilic molecules through the epidermis to the dermis. On the other hand, a new approach called low-intensity CAP (LICAP) has been developed, allowing the plasma level to be controlled within a subtoxic range, thereby demonstrating various biological benefits without tissue damage. However, the ability of LICAP to enhance transepidermal delivery in sub-cytotoxic conditions has not been fully investigated. This study aims to determine the sub-cytotoxic range of exposure time for LICAP and, within the range, to investigate the effects of LICAP treatment on transepidermal drug delivery (TED) and mechanisms using human keratinocytes and a mouse model. For the in vitro studies, LICAP treatment was evaluated in human keratinocyte (HaCaT) cells by assessing reactive species production, DNA damage, and cytotoxicity profiles. Within the determined safety range, mechanistic analyses were conducted to examine LICAP-enhanced delivery pathways. mRNA expression and protein levels of tight and adherens junction genes were quantified, and changes in ultramicroscopic morphology of HaCaT monolayers were investigated. Intracellular delivery of fluorescein isothiocyanate (FITC)-dextran was also assessed. For the in vivo studies, E-cadherin expression and the transepidermal delivery (TED) of human epidermal growth factor (hEGF) were analyzed in LICAP-treated mouse dorsal skin. The upper safety range of LICAP exposure time, reducing cell viability by 70% (IC70 or LD30), was estimated at 34.3 s. Within the safety range, LICAP treatment downregulated multiple tight and adherens junction genes in HaCaT cells. Consistent with the in vitro results, the epidermal E-cadherin expression was reduced, and human epidermal growth factor (hEGF) was infiltrated in the dermis of the LICAP-treated mouse skin. Intercellular clefts were detected in the HaCaT cell monolayer immediately following LICAP treatment and intracellular delivery of FITC-dextran was confirmed after LICAP exposure. This study demonstrated that LICAP treatment enhances transepidermal permeation of hEGF, apparently via both paracellular and transcellular routes. Under our study conditions, LICAP treatment seems to be a novel approach to facilitate TED with low safety concerns in vitro. Further translational studies are needed for clinical evaluation.